Practical torque sensorless super-twisting control of manipulators based on a novel integral non-singular fast terminal sliding mode with fixed-time convergence. (3rd April 2023) - Yazdani, Mohammad; Ganjefar, Soheil
ABSTRACT: In this paper, a robust controller has been proposed for first-order uncertain non-linear systems by introducing a novel hybrid sliding surface. Using this method, contrary to previous proposed sliding surfaces, the state trajectory begins moving on the correct sliding mode and the reaching phase can be reduced to the minimum time. Thus, the transient response speed of the system and consequently the efficiency and robustness of the system increase. Moreover, the convergence of the system state in bounded time, independent of the initial conditions of the system, is guaranteed without singularity problems. Then, for torque sensorless control of permanent-magnet DC motors, as one of the most prevalent joint actuators in robotics, an adaptive super-twisting controller, based on the proposed hybrid sliding surface, has been presented. Using this method, continuous finite-time control of the DC motor's torque without a torque sensor is realized. The DC motor load-side torque is estimated based on an adaptive wavelet neural network and it is compensated in the control loop. In addition to the stability proof and fixed-time convergence of control schemes, a set of simulation and experimental studies have been provided to evaluate the efficiency of control algorithms and investigate their feasibility. GRAPHICAL ABSTRACT: UF0001